Fabrication, Applications and Future Prospects of Mesoporous Silica Nanoparticles - Fatema Zohera; Farahidah Mohamed; Abul Kalam Azad; May Kyaw Oo (IIUM Press, International Islamic University Malaysia, 2024)
In past decades, nanomedicine has become a prominent area of focus within the discipline of nanotechnology, eliciting significant anticipation within the field of biomedical research. Scientists are creating unique nanoparticles for diagnosis, utilising techniques for imaging as well as therapy applications using medication delivery techniques. Mesoporous silica nanoparticles (MSNs), a recent addition to this area, serve as a sterling example of innovative nanostructures that offer distinctive and exceptional features. These features make them valuable for developing drug delivery systems with consistent and positive advancements in preclinical. MSNs efficiently encapsulate, control, and sometimes deliver biologic agents intracellularly for clinical use due to their distinct physicochemical characteristics, such as high porosity, large surface area, adjustable pore size and dimensions, good biocompatibility, and significant loading capacity. In this article, we discuss the latest advancements in fabrication, their presumed usefulness in delivering medications, and their application as diagnostic tools. It has been demonstrated that silica can store and release therapeutics, such as antibiotics, in a sustained and controlled manner. The desirable properties of MSNs have been further enhanced by modifying the surface of the siliceous frameworks through incorporating supramolecular assemblies and various metal species and their conjugates. These substantial advancements in innovative colloidal inorganic nanocontainers have driven researchers to explore their use in novel applications, such as stimuli (light/ultrasound/ magnetic)-responsive delivery-associated therapies with exceptional in vivo performance. This article provides a brief overview of the fabrication of siliceous frameworks and discusses significant advances in the engineering of MSNs.  The precise control of the shape, dimension, homogeneity, and dispersity of MSNs is crucial, as these characteristics are critical quality attributes necessary for regulatory approval. Currently, explicit FDA guidelines for developing nanomaterial-based formulations intended for diagnostic or therapeutic purposes are lacking. Therefore, establishing standardised protocols and techniques for the synthesis and characterisation of nanoparticles, particularly for their use as theranostics, is essential for future commercial potential.